What do roots do? - Kudlinski, Kathleen V.; Schuppert, David (Minnetonka, MN : NorthWord Books for Young Readers, 2005)
Presents a children's rhyming text for early readers that describes different kinds of roots and what they do for plants.
Library Media Connection
School Library Journal
Science Books & Films (A.A.A.S.)
2.4
K-3.
K-3
Keywords: Roots (Botany) -- Juvenile literature; Roots (Botany); Roots (Botany)